Innovative Potential of the Knowledge-Intensive Services Sector in Russia - Marina Doroshenko (Foresight and STI Governance)
Knowledge-intensive services (KIS), described in a large qualitative literature, are essential to high innovation performance and are thus one of the key segments of the knowledge economy. This paper addresses theinnovative capacity of the KIS from data obtained from an annual monitoring survey of the KIS sector performed by the HSE ISSEK since 2006.It shows that the evolution of the KIS sector is dominated by  two vectors, aimed respectively at standardizing and customizing services. The latter is especially gaining momentum–distinctiveness is a key competitive advantage for a service provider and is likely to remain so, as innovative and diversified production expand. Also, the recent financial and economic crisis significantly spurred service firms’ innovation activity.